2002
DOI: 10.1258/0022215021910276
|View full text |Cite
|
Sign up to set email alerts
|

Growth of laryngeal glands in infants: a comparative study of the sub- and supraglottic larynx

Abstract: It is well established that laryngeal secretions, produced in the glandular tissue, contribute to the local defence system of the larynx. In this study, the distribution of glandular tissues in the subglottic and supraglottic larynx was examined in 55 infants, using an image analysing system. The average area of the mucosa or glandular acini at the level of the false vocal fold was almost three times larger than that of the subglottis. At both levels, the area occupied by the glands increased according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…During foetal life, at the level of the glandular epithelium, the production of a key protein for the mucosal immune system starts [49][50][51] . However, only in the post-natal period glands play a major role in the production of immunoglobulins 52 . Glandular concentration and distribution in laryngeal tract increase during childhood and achieve their maximum level when larynx completes its anatomical development.…”
Section: Pharyngo-laryngeal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…During foetal life, at the level of the glandular epithelium, the production of a key protein for the mucosal immune system starts [49][50][51] . However, only in the post-natal period glands play a major role in the production of immunoglobulins 52 . Glandular concentration and distribution in laryngeal tract increase during childhood and achieve their maximum level when larynx completes its anatomical development.…”
Section: Pharyngo-laryngeal Tractmentioning
confidence: 99%
“…At the laryngeal tract, in fact, secretion that is fundamental for the lubrication of mucosa also plays an important role for phonation. Ichikawa 55 performed photodynamic studies on a group of patients in order to evaluate the effects of the quantity and quality of mucus on the voice, concluding that viscosity of secretions has an impact on phonation. The Author assumes that morpho-functional changes in laryngeal salivary glands result in a quantitative reduction in secretions leading to a change in laryngeal viscosity and lubrication.…”
Section: Pharyngo-laryngeal Tractmentioning
confidence: 99%
“…[1][2][3][4][5] Recent advances in immunology and immunopathology have revealed that the larynx possesses an active mucosal immune system, as do other respiratory organs. 2 We have studied the development of glandular tissue within the mucosal defence system in the human adult and infant larynx.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused particularly on the development of the laryngeal glands. [3][4][5] However, in spite of the laryngeal mucosal defences, human papilloma virus (HPV) often infects, and proliferates within, the laryngeal mucosa. In addition, high risk HPV types 16 and 18 play an important role in carcinogenesis within the larynx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation